ANALISIS PENGARUH HARGA TIKET DAN AKSESIBILITAS TERHADAP MINAT WISATAWAN BERKUNJUNG PADA OBJEK WISATA PUNCAK LAWANG KABUPATEN AGAM - Rifa Khairunnisa; Novera Martilova (CV. Adiba Aisha Amira, 2023)
Indonesia is one of the countries that has a variety of tourist attractions caused by culture, customs, and others. Agam Regency is one of several regencies or cities in the province of West Sumatra. One of the tourist destinations the attention of tourists is the Puncak Lawang. Puncak Lawang is located on a plateau peak with an altitude of 1,250 meters above sea level, precisely in Matur District, Agam Regency, West Sumatra. Puncak Lawang has the advantage of beautiful scenery surrounded by pine forests and cool air. The number of tourists visiting the Puncak Lawang tourist attraction has increased and decreased every year which makes the background for researchers to take this research. Therefore, researchers take several factors based on observations that researchers have made. The factors are ticket prices and accessibility to the interest of tourists visiting Puncak Lawang Tourism Objects. This study was conducted to determine how much influence ticket prices and accessibility have on tourist interest in visiting. The research method used is a quantitative approach. The study population is tourists visiting the Puncak Lawang Tourism Object. The sample in this study was 100 respondents. The data collection instrument is a questionnaire. Data analysis techniques use multiple linear analysis. The results showed that: (1) ticket prices are positively related and affect the interest of tourists visiting Puncak Lawang Tourism Objects. (2) Accessibility is positively related and affects the interest of tourists visiting Puncak Lawang Tourism Object. (3) Price and accessibility simultaneously affect the interest of visiting tourists.